Mental Maps and Information Surfaces in Québec and Ontario - Gould, Peter; Lafond, Nicole (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1979)
Maps of residential desirability and information surfaces in Québec and Ontario vary consider-ably between children and young adults in the two provinces. Such differences reflect variations in migration, education and economic factors. Difficult methodological questions are raised concerning the measurement of cultural and linguistic barrier effects.